2016
DOI: 10.1103/physreva.94.042104
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty relations for general unitary operators

Abstract: We derive several uncertainty relations for two arbitrary unitary operators acting on physical states of a Hilbert space. We show that our bounds are tighter in various cases than the ones existing in the current literature. Using the uncertainty relation for the unitary operators we obtain the tight state-independent lower bound for the uncertainty of two Pauli observables and anticommuting observables in higher dimensions. With regard to the minimum uncertainty states, we derive the minimum uncertainty state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…(1) was improved by Schrödinger [5]. Recently, variancebased uncertainty relations have been intensely studied in [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Because of their relevance in quantum information theory, the entropies [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] have been employed to quantify the uncertainty relations between incompatible observables.…”
Section: Introductionmentioning
confidence: 99%
“…(1) was improved by Schrödinger [5]. Recently, variancebased uncertainty relations have been intensely studied in [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Because of their relevance in quantum information theory, the entropies [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] have been employed to quantify the uncertainty relations between incompatible observables.…”
Section: Introductionmentioning
confidence: 99%
“…There exist two kinds of operators in quantum mechanics: Hermitian and non-Hermitian operators, but it should be paid particular attention that the previous uncertainty relations are contradictory with the non-Hermitian operators, i.e., lots of uncertainty relations will be violated when applied to non-Hermitian operators [68][69][70] 2 for all qubit systems, where the non-Hermitian operator σ + (σ − ) is the raising (lowering) operator of the single qubit system. That is to say, different from the Hermitian operators, the uncertainties of the non-Hermitian operators are not lower-bounded by the quantities related with the commutator and anti-commutator.…”
Section: The Applicability Of the Unified And Exact Framework To Non-mentioning
confidence: 99%
“…In 2014, Mcconne and Pati [27] proposed a sum form of variancebased uncertainty relation, which captures the essence of noncommutativity and also raises the question of compatibility (see [28] for further discussion). In [29] the sum form was strengthened considerably. In [30] the authors showed that there are no nontrivial unconditional joint-measurement bounds for state-dependent errors in the conceptual framework, while Heisenberg-type measurement uncertainty relations for state-independent errors have been proven (cf.…”
Section: Introductionmentioning
confidence: 99%